Orthophotomosaics of Gorgona Island coral reefs - Juan Carlos Mejía-Rentería; Jaime R Cantera-Kintz; Fernando A Zapata (PANGAEA, 2024)
Here we present a photogrammetric reconstruction of the best developed coral reefs of the Colombian Pacific, located at Gorgona Island. A shapefile containing the detail of coral reef boundaries, used to calculate areas is also included. Dataset includes four (4) orthophotomosaics (GeoTIFF) of the next coral reefs : La Azufrada, Playa Blanca, Arrecifito, Old Pier, and one (1) shapefile.